Folksonomies : indexing and retrieval in Web 2.0 - Peters, Isabella (Knowledge & information., 2009)
In Web 2.0 users make heavy use of collaborative information services to create, publish, and share digital information resources. They also index and represent these resources via their own keywords, called tags. The sum of this user-generated metadata is also called a ‘folksonomy’. In contrast to professionally created and highly structured metadata, e.g. subject headings, thesauri, classification systems or ontologies which are applied in libraries, corporate information architectures, or commercial databases and which were developed according to defined standards, tags can be freely chosen by users and attached to any information resource. As one type of metadata, folksonomies provide access to information resources and serve users as retrieval tool for their own resources and to find data of other users. The book delivers insights into typical applications of folksonomies, especially within collaborative information services, and discusses the strengths and weaknesses of folksonomies as tools of knowledge representation and information retrieval. It aims at providing conceptual considerations for solving problems of Folksonomies and presents how established methods of knowledge representation and information retrieval can successfully be transferred to them.